'White Mars' – nearly two decades of biomedical research at the Antarctic Concordia station. Issue 1 (27th July 2020) - Van Ombergen, Angelique; Rossiter, Andrea; Ngo‐Anh, Thu Jennifer
Abstract : New Findings: What is the topic of this review? Biomedical research at the Antarctic Concordia Station. What advances does it highlight? Overview of findings in psychology, neuroscience, sleep, cardiovascular physiology and immune system, relevant in isolated, confined and extreme environments and spaceflight. Abstract: Extended stays in isolated, confined and extreme (ICE) environments like Antarctica are associated with a whole set of psychological and physiological challenges for the crew. As such, winter‐over stays at Antarctica provide an important opportunity to acquire knowledge into the physiological and psychological changes that ICE environments inevitably bring. The European Space Agency (ESA) is particularly interested in conducting research in such an environment, as it is a unique opportunity to translate these results to space crews experiencing very similar issues. In the past two decades, the ESA has supported a total of 36 biomedical research projects at the Concordia station in collaboration with the French and Italian polar institutes. More specifically, studies in the areas of psychology, neuroscience, sleep physiology, cardiovascular physiology and immunology were performed. The outcomes of these studies are directly relevant for people working in ICE environments, but also help to better understand the biomedical challenges of those environments. Consequently, they can help to better prepare for human space exploration and to identify countermeasures to minimize the adverse effects of space environments on astronaut health. The aim of this review is to provide an overview of the biomedical studies that have taken place in the past two decades at the Antarctic Concordia station and to summarize the results and their implication for human spaceflight. Abstract :